A tour of the imaginary of revolution through the Curricular Pensum of the School of Sociology of the Central University of Ecuador - Pilca, Patricio (2022)
This article traces the development of the thinking of the School of Sociology and Political Science [ESCP] at the Central University of Ecuador from the 1960s onwards. The first moment was when the sociological field was closely linked to anthropology. The second moment was when critical thought arose and positioned itself, where Marxism was its central axis, and revolution its clearest possibility. Finally, in its third moment, sociological thought was anchored in the technical-professional. In methodological terms, this journey was possible from the review of academic curricula, since they are the devices where the training of sociologists is materialized, but, in addition, it is there where the theories that were discussed at each historical moment are shown.